Extreme drought-heatwave exacerbates water quality deterioration in China - Jie Jiang; Zhaoli Wang; Zhenxing Zhang; Xushu Wu; Chengguang Lai; Zhaoyang Zeng; Xiaohong Chen (Ecological Indicators)
Extreme drought-heatwaves can severely impact river water quality, yet the relationships and drivers underlying these effects remain poorly understood. This study employed data-driven analyses to explore how water quality change is affected by extreme drought-heatwave events, with a focus on identifying the key hydrometeorological drivers. The unprecedented extreme drought-heatwave event in China from March to December in 2022 provides an ideal case study. The spatiotemporal development was characterized by using meteorological drought index and drought centroid tracking, and the responses of nine water quality constituents to this event were quantified. Results revealed that the drought-heatwave was jointly driven by a significant decrease in precipitation (up to ∼50 % less than usual) and sustained high temperatures (∼2 °C above normal). Water quality deteriorated notably during this event, evidenced by ever-increased total nitrogen (TN) concentration (∼25 % to ∼30 % higher than non-drought period), higher TN extremes (27.5 mg/L), and decreased dissolved oxygen (DO) (∼−1.0 to ∼−0.5 mg/L lower than non-drought). Northern and central China particularly suffered from severe deterioration, concentrating 71 % of TN loads during the drought period, with a steeper TN load increase than in non-drought periods. Behind water quality degradation, air temperature emerged as the predominant driver of water quality deterioration, followed by streamflow and precipitation, with correlation coefficients (R) between temperature and TN/DO ranging from −0.74 to −0.59. This study revealed that extreme drought-heatwave event critically deteriorate river water quality in China, highlighting the urgent need for adaptive strategies to protect and restore water quality during extreme drought-heatwave events.